Determinants of Financial Inclusion in OIC Countries - Zainorin, Nur Diniey Ezzati; Jalaludin, Syuhada; Abdul Aziz, Nor Farradila; Balasingam, Balachandran (Information Management and Business Review, 2023)
The OIC countries have endorsed financial inclusion as part of their initiatives to uphold the interests of the Muslim world. However, they experience the greatest levels of financial system exclusion, as they are found to have a lower percentage of access to formal bank accounts. Therefore, this study aims to investigate the determinants of financial inclusion in OIC nations. Macroeconomic factors (GDP and the money supply) and bank variables (non-performing loans and the number of internet users) covering the year 2011 to 2020 from 40 OIC nations are included in this paper. Using panel data, the results indicate that both bank variables are positively significant in determining financial inclusion for OIC countries. No significant relationship is found between studied macroeconomic factors and financial inclusion.